2023
DOI: 10.1186/s13059-023-02883-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MLL3/4 decouples enhancer H3K4 monomethylation, H3K27 acetylation, and gene activation during embryonic stem cell differentiation

Abstract: Background Enhancers are essential in defining cell fates through the control of cell-type-specific gene expression. Enhancer activation is a multi-step process involving chromatin remodelers and histone modifiers including the monomethylation of H3K4 (H3K4me1) by MLL3 (KMT2C) and MLL4 (KMT2D). MLL3/4 are thought to be critical for enhancer activation and cognate gene expression including through the recruitment of acetyltransferases for H3K27. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…We reasoned that if the cell cycle phase plays a strong role during the exit from naive pluripotency, then an extension in the cell cycle length should lead to a delay in differentiation. Boileau et al recently investigated the differentiation behaviour of MLL3/4 DKO and MLL3 KO mESCs 38 . The KOs showed a strong delay in proliferation, however, loss of the chromatin modifiers had little effect on the overall exit from naive pluripotency, suggesting that extension of cell cycle length does not interfere with differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that if the cell cycle phase plays a strong role during the exit from naive pluripotency, then an extension in the cell cycle length should lead to a delay in differentiation. Boileau et al recently investigated the differentiation behaviour of MLL3/4 DKO and MLL3 KO mESCs 38 . The KOs showed a strong delay in proliferation, however, loss of the chromatin modifiers had little effect on the overall exit from naive pluripotency, suggesting that extension of cell cycle length does not interfere with differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed conversely, H3K27 acetylation is dispensable for binding of the transcriptional machinery to chromatin in mESCs and for transcriptional activation during early differentiation [ 111 ]. A recent study also showed that gene transcription is not compromised during mESCs differentiation by the absence of H3K4me1 [ 108 ]. These observations suggest that histone modifications at loci displaying chromatin memory may be the by-product of RNA Pol II and TF occupancy, rather than be actively promoting their recruitment and the maintenance of a chromatin accessible state.…”
Section: Potential Molecular Mechanisms For the Establishment And Mai...mentioning
confidence: 99%
“…that they are the bi-product of transcription [107][108][109][110][111]. For instance, in yeast, the presence of RNAPII at transcriptionally active sites can promote the recruitment and activity of histone acetyltransferases and favor histone acetylation [107].…”
Section: Histone Modifications and Variantsmentioning
confidence: 99%
“…H3K4me1 was among the best overall predictors of early steady-state naïve RT and earlier RT changes during differentiation yet a causal role for this epigenetic histone modification or the responsible enzymes in the regulation of RT remains unexplored. H3K4me1 is commonly thought of as a marker of either primed or active enhancers that control the expression of their cognate genes 30. The MLL3/4 (also known as KMT2C/D) enzymes are responsible for the H3K4 monoand dimethylation at many of these enhancers 31,32 with MLL4 being the predominantly active isoform in ES cells 33,34 . Surprisingly, the loss of MLL3/4 has little impact on the establishment of a formative transcriptional program during ES cell differentiation 34 .…”
Section: Mll3/4 Activity Is Essential For Genome-wide Rt Dynamics Dur...mentioning
confidence: 99%